2016
DOI: 10.5539/jpl.v9n7p142
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Malaysian Experience: Overcoming the Regulatory Challenges in the Nascent Takaful Practice Innigeria

Abstract: The Islamic insurance (Takaful) introduced in March, 2013, was specifically meant to bridge the endemic insurance gap in Nigeria by engendering deepening insurance penetration and financial inclusion of the hitherto underserved and uninsured huge Muslim clientele. However, the Takaful Operational Guidelines and a host of other enabling insurance instruments are caught up in a web of regulatory conflict and ambiguity. The legal effect of this is a huge regulatory vacuum that is bound to impact negatively on cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Their study adopted the existing model of DTPB from the family Takaful perspective. Saleh, Balan, and Ruslan (2016) examined the attributes of learning from the Malaysian experience: Overcoming the regulatory challenges in the nascent Takaful practice in Nigeria. The authors revealed that Islamic insurance (Takaful), introduced in March 2013, was specifically meant to bridge the endemic insurance gap in Nigeria by engendering deepening insurance penetration and financial inclusion of the hitherto underserved and uninsured huge Muslim client.…”
Section: Background Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Their study adopted the existing model of DTPB from the family Takaful perspective. Saleh, Balan, and Ruslan (2016) examined the attributes of learning from the Malaysian experience: Overcoming the regulatory challenges in the nascent Takaful practice in Nigeria. The authors revealed that Islamic insurance (Takaful), introduced in March 2013, was specifically meant to bridge the endemic insurance gap in Nigeria by engendering deepening insurance penetration and financial inclusion of the hitherto underserved and uninsured huge Muslim client.…”
Section: Background Theorymentioning
confidence: 99%
“…This study empirically examined the proposed research model containing three latent variables (i.e., patronage determinants), whereas awareness, perception, and religiosity were the independent variables, and patronage was the only dependent variable. All scales and measures used in this research were adapted from the studies (Aziz, Husin and Husin, 2017;Saleh, Balan and Ruslan, 2016;Maiyaki & Ayuba, 2015;Yaqub and Dandago, 2015).…”
Section: Model Developmentmentioning
confidence: 99%
“…Previous studies, (already highlighted in the introduction to this research) have either provided insight on the workings of the frameworks within the jurisdictions of the various Takaful industries, or have made some attempt to compare the efficacy of one system against the other without necessarily focusing on Takaful. Without a doubt Saleh et al (2016) provide extensive research on the regulatory lacunae evident in the Nigerian framework by comparing it to that available in Malaysia. The study however only highlights the ambiguities and irregularities within all laws regulating Takaful in Nigeria.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Khan and Shah (2015) comparatively analyze the regulatory and supervisory structures for the Islamic financial sector in Malaysia, Pakistan, Bahrain and the UK but the scope was limited to the Islamic banking sector. Saleh et al (2016) recognize the similarities between the Nigerian and Malaysian Takaful regulatory frameworks and the possibilities of Nigeria learning from that of Malaysia. However, they did not conduct an in-depth analysis of both systems.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation